2017
DOI: 10.1038/s10038-017-0371-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of HMGB3 by antitumor miR-205-5p inhibits cancer cell aggressiveness and is involved in prostate cancer pathogenesis

Abstract: Our recent determination of a microRNA (miRNA) expression signature in prostate cancer (PCa) revealed that miR-205-5p was significantly reduced in PCa tissues and that it acted as an antitumor miRNA. The aim of this study was to identify oncogenic genes and pathways in PCa cells that were regulated by antitumor miR-205-5p. Genome-wide gene expression analyses and in silico miRNA database searches showed that 37 genes were putative targets of miR-205-5p regulation. Among those genes, elevated expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 45 publications
0
77
0
2
Order By: Relevance
“…We used 2 human RCC cell lines (786‐O and A498) obtained from ATCC (Manassas, VA, USA) as previously described . These cell lines were maintained in RPMI‐1640 with 10% FBS (HyClone, Logan, UT, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used 2 human RCC cell lines (786‐O and A498) obtained from ATCC (Manassas, VA, USA) as previously described . These cell lines were maintained in RPMI‐1640 with 10% FBS (HyClone, Logan, UT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from human tissues and cell lines using TRIzol reagent (Invitrogen) according to the manufacturer's protocol, as we described previously . The procedure for PCR quantification has been outlined.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial study on HMGB3 revealed that it participated in regulating the balance between self-renewal and differentiation in hematopoietic stem cells (11). The oncogenic potential and prognostic value of HMGB3 in different cancer types has also been appreciated (34,35).…”
Section: Discussionmentioning
confidence: 99%